2012
DOI: 10.1007/s10163-012-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic pretreatment of waste on the rate of anaerobic treatment processes

Abstract: The efficiency of waste degradation can be expressed by the rate of waste decomposition in individual phases. This article presents the durations of degradation phases of pretreated and untreated waste stabilized in anaerobic laboratory reactors. In this investigation, the quantities of organic and nitrogen contaminants emitted from the waste during the study are presented. The study confirmed the beneficial effects of aerobic pretreatment of waste before landfilling on reducing the duration of hydrolysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This causes the reduction of BOD concentrations by two orders of magnitude, with final values of 200 mg/L in the monitoring period. The average concentrations of COD observed in this study are consistent with those achieved by Suchowska-Kisielewicz et al (2013), who reported values of 23,500 mg/L during the unstable methanogenic phase. Taking these authors' results into account, the stable phase (in which measured COD concentrations were 1,300 mg/L) has not yet been reached in this research.…”
Section: Compositionsupporting
confidence: 92%
“…This causes the reduction of BOD concentrations by two orders of magnitude, with final values of 200 mg/L in the monitoring period. The average concentrations of COD observed in this study are consistent with those achieved by Suchowska-Kisielewicz et al (2013), who reported values of 23,500 mg/L during the unstable methanogenic phase. Taking these authors' results into account, the stable phase (in which measured COD concentrations were 1,300 mg/L) has not yet been reached in this research.…”
Section: Compositionsupporting
confidence: 92%
“…The differences in the biological methods of composting, stabilization and biodrying are not only in the operational variables but also in the final destination of the outputs. The final product of the stabilization can be treated as a stable and non-biologically active material that can be landfilled with minimum environmental impact [4][5][6][7][8][9][10][11][12][13][14]. In the biodrying reactor only a part of the easy biodegradable fraction is being decomposed in order to save the calorific value as the production of input to the refuse derived fuel RDF is the main target.…”
Section: Introductionmentioning
confidence: 99%